GEOGRAPHICAL – HISTORICAL PATTERNS OF ROMANIAN IDENTITY - Dr. Petre Gheorghe BÂRLEA (Diversitate si Identitate Culturala in Europa)
The present study expounds a synthesis of the main cultural models leading to the present-day configuration of Romanian cultural identity. We start from the assumption that cultural identity is a construct, an ever-evolving process involving not only objective, externally induced factors, but also elements of willfulness. This perspective of analysis, also adopted by historians and cultural studies specialists, is based on the perception that the geographical location and historical events impinging on Romanian society along the centuries have created a matrix defining some of the present features of Romanian identity.